First report of carglumic acid in a patient with citrullinemia type 1 (argininosuccinate synthetase deficiency). (25th July 2017) - Kose, E.; Kuyum, P.; Aksoy, B.; Häberle, J.; Arslan, N.; Ozturk, Y.
Summary: What is known and objective: Carglumic acid is a structural analogue of human N‐acetylglutamate, which has become an alternative therapeutic option for hyperammonaemia in organic acidaemias such as isovaleric acidaemia, methylmalonic acidaemia and propionic acidaemia, and it has been suggested in other urea cycle disorders such as ornithine transcarbamylase deficiency and carbamoyl phosphate synthetase 1 deficiency. Case description: A male newborn was diagnosed with citrullinemia after serum amino acid analyses revealed markedly elevated citrulline concentration together with homozygous p.Gly390Arg mutation in ASS1 gene. The ammonia concentration decreased and blood gas analysis normalized after peritoneal dialysis was performed for three days. Also, sodium benzoate, L‐arginine and parenteral nutrition with glucose and lipid therapy were initiated. Until 1 year of age, low adherence to sodium benzoate therapy due to unpleasant taste caused hyperammonaemic episodes and obligated us to initiate carglumic acid (100 mg/kg/day) therapy. During treatment with carglumic acid, the median ammonia level was 45.6 µmol/L. The patient's treatment was switched from carglumic acid to sodium phenylbutyrate when he was 4.5 years old. Currently, the patient is 6.5 years old and remains under follow‐up with sodium phenylbutyrate, L‐arginine and protein‐restricted diet. Plasma ornithine level was found to be significantly lower during the carglumic acid treatment compared to other treatments ( P =.039). Also, glutamic acid was found to be higher during the sodium benzoate treatment period compared to other treatment periods ( P =.024). What is new and conclusion: To the best of our knowledge, this is the first report describing the long‐term use of carglumic acid in a patient with argininosuccinate synthetase deficiency. Abstract : In the analysis of laboratory findings of the patient, there were no differences in median ammonia, citrulline and glycine levels between the sodium benzoate, carglumic acid and sodium phenylbutyrate treatments. Ornithine level was found to be significantly lower during the carglumic acid treatment compared to other treatments ( P =.039). Also, glutamic acid was found to be higher during the sodium benzoate treatment period compared to other treatment periods ( P =.024).